2006
DOI: 10.1111/j.1752-1688.2006.tb06029.x
|View full text |Cite
|
Sign up to set email alerts
|

LAKE WATER QUALITY ASSESSMENT FROM LANDSAT THEMATIC MAPPER DATA USING NEURAL NETWORK: AN APPROACH TO OPTIMAL BAND COMBINATION SELECTION1

Abstract: The concern about water quality in inland water bodies such as lakes and reservoirs has been increasing. Owing to the complexity associated with field collection of water quality samples and subsequent laboratory analyses, scientists and researchers have employed remote sensing techniques for water quality information retrieval. Due to the limitations of linear regression methods, many researchers have employed the artificial neural network (ANN) technique to decorrelate satellite data in order to assess water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 18 publications
(18 reference statements)
1
43
0
3
Order By: Relevance
“…Sudheer et al (2006) has demonstrated that significant influencing variables can be used for modeling a water-quality parameter using ANN models. Mabwoga et al (2009) assessed the water quality of Harike wetland in India using satellite imagery from the Indian Remote Sensing Satellite, Resourcesat (IRS P6).…”
Section: Introductionmentioning
confidence: 99%
“…Sudheer et al (2006) has demonstrated that significant influencing variables can be used for modeling a water-quality parameter using ANN models. Mabwoga et al (2009) assessed the water quality of Harike wetland in India using satellite imagery from the Indian Remote Sensing Satellite, Resourcesat (IRS P6).…”
Section: Introductionmentioning
confidence: 99%
“…However, there exist numerous remote sensing-based studies in the related literature that monitor optically active water quality variables such as turbidity, S depth , Chl-a, suspended matter, temperature, and colored dissolved organic matter (Dekker and Peters 1993;Lavery et al 1993;Zhang et al 2003;Kutser et al 2005;Sudheer et al 2006;Koponen 2006; Alparslan et al 2007;Sass et al 2007;Giardino et al 2007). …”
Section: Resultsmentioning
confidence: 98%
“…In recent years, the ANN technique, which is a data driven modelling tool, has become an increasingly popular tool for water quality modelling among researchers and practicing engineers (e.g. Keiner and Yan, 1998;Gross et al, 1999;Sciller et al, 1999;Tanaka et al, 2000;Baruah et al, 2001;Panda et al, 2004;Gatts et al, 2005;Sudheer et al, 2006). Nonetheless, since ANN is a data demanding approach for model development, the uncertainty associated with the ANN models developed in data scarce situations may be very high, and the robustness of any model application will be affected.…”
Section: Introductionmentioning
confidence: 99%